Individens plats i den kyrkohistoriska forskningen - Ingvar Bengtsson (Svensk Teologisk Kvartalskrift, 2025)
The individual is given a central position in this article on church history research. To some extent, it is an article about the individual as a research object, but primarily about the individual as a subject in the research and his or her path through the sometimes difficult landscape of research. First, an introduction is given with some connection to previous research and some terminological delimitations. The fundamental importance of the researcher’s own gaze and location is emphasised. Thereafter, glimpses are given at the individual level from the context and change of a researcher and a research project. What factual and individual factors are crucial to the research process? Examples are given of when obstacles have appeared and confusion has arisen. Concretely, the article illustrates the highly individual context of a research project that reached the end of the road and was therefore, initially completely unplanned, divided into two separate projects, which led onto roads that each required several extensive new investments. An important aspect of the article is what results a psychotherapeutic education and practice can have in the subject of church history. What do these two disciplines have in common and in what way can they be combined with each other? Two such research results are cited. One is a theological doctoral dissertation on Psychoanalysis and Christian faith. The other is a scientific work from a psychological point of view offering a study in Psychoanalysis and History.